Ultrafast imaging of photochemical dynamics: Royal Society of Edinburgh, UK, 31 August-2 September 2016 ; Chair: Adam Kirrander (University of Edinburgh), Russell Minns (University of Southampton) - Kirrander, Adam; Minns, Russell; Copsey, May (Faraday discussions, 2016)
This volume focuses on ultrafast imaging of photochemical dynamics covering the development of new techniques and advances in theoretical modelling of quantum dynamics. Photochemical reactions have tremendous scientific importance, ranging from photosynthesis to atmospheric reactions, and technologies such as sensors or displays. Due to the intrinsic complexity of photochemical reactions, they remain the least understood type of chemical process. Nonadiabatic dynamics, ultrafast time-scales, quantum effects and conical intersections are known to be important, but a detailed comprehension remains elusive. However, new experimental techniques capable of monitoring photochemical processes in unprecedented detail are appearing. This includes the development of intense-laser techniques, the construction of freeelectron lasers such as the XFEL in Europe and the LCLS in the USA, new sources of pulsed electrons, advanced detection techniques, and important advances in theoretical modelling of quantum dynamics. Many of these techniques are developed by research communities not traditionally concerned with photochemistry, but provide an opportunity to shed new light on photochemical dynamics
"A general discussion on Ultrafast Imaging of Photochemical Dynamics was held in Edinburgh, UK on the 31st of August and 1st and 2nd of September 2016"--Page 5
Includes bibliographical references
Keywords: Konferenzschrift -- 31.08.2016-02.09.2016 -- Edinburgh; Laserchemie